Left Atrial Appendage Closure with Amplatzer Cardiac Plug in Nonvalvular Atrial Fibrillation: Safety and Long-Term Outcome - Costa,Marcio José Montenegro da (2017)
Abstract Background: Atrial fibrillation (AF) is a cardiac arrhythmia with high risk for thromboembolic events, specially stroke. Objective: To assess the safety of left atrial appendage closure (LAAC) with the Amplatzer Cardiac Plug for the prevention of thromboembolic events in patients with nonvalvular AF. Methods: This study included 15 patients with nonvalvular AF referred for LAAC, 6 older than 75 years (mean age, 69.4 ± 9.3 years; 60% of the male sex). Results: The mean CHADS2 score was 3.4 ± 0.1, and mean CHA2DS2VASc , 4.8 ± 1.8, evidencing a high risk for thromboembolic events. All patients had a HAS-BLED score > 3 (mean, 4.5 ± 1.2) with a high risk for major bleeding within 1 year. The device was successfully implanted in all patients, with correct positioning in the first attempt in most of them (n = 11; 73.3%). Conclusion: There was no periprocedural complication, such as device migration, pericardial tamponade, vascular complications and major bleeding. All patients had an uneventful in-hospital course, being discharged in 2 days. The echocardiographic assessments at 6 and 12 months showed neither device migration, nor thrombus formation, nor peridevice leak. On clinical assessment at 12 months, no patient had thromboembolic events or bleeding related to the device or risk factors. In this small series, LAAC with Amplatzer Cardiac Plug proved to be safe, with high procedural success rate and favorable outcome at the 12-month follow-up. (Arq Bras Cardiol. 2017; [online].ahead print, PP.0-0)